Comprehensive analysis of CDKN2A (p16INK4A/p14ARF) and CDKN2B genes in 53 melanoma index cases considered to be at heightened risk of melanoma. Issue 1 (3rd June 2005) - Laud, K; Marian, C; Avril, M F; Barrois, M; Chompret, A; Goldstein, A M; Tucker, M A; Clark, P A; Peters, G; Chaudru, V; Demenais, F; Spatz, A; et al.
Abstract : Objective: Comprehensive analysis of the 9p21 locus including the CDKN2A, ARF, and CDKN2B genes in 53 individuals from melanoma index cases considered to be at heightened risk of melanoma. Methods and Results: Using a combination of DNA sequencing, gene copy number by real time quantitative PCR, linkage analysis, and transcript analysis in haploid somatic cell hybrids, we found no evidence for germline alteration in either coding or non-coding domains of CDKN2A and CDKN2B . However, we identified a p14 ARF exon 1β missense germline mutation (G16D) in a melanoma-neural system tumour syndrome (CMM+NST) family and a 8474 bp germline deletion from 196 bp upstream of p14 ARF exon 1β initiation codon to 11233 bp upstream of exon 1α of p16 INK4A in a family with five melanoma cases. For three out of 10 families with at least three melanoma cases, the disease gene was unlinked to the 9p21 region, while linkage analysis was not fully conclusive for seven families. Conclusions: These data reinforce the hypothesis that ARF is a melanoma susceptibility gene and suggest that germline deletions specifically affecting p14 ARF may not be solely responsible for NST susceptibility. Predisposition to CMM+NST could either be due to complete disruption of the CDKN2A locus or be the result of more complex genetic inheritance. In addition, the absence of any genetic alteration in 50 melanoma prone families or patients suggests the presence of additional tumour suppressor genes possibly in the 9p21 region, and on other chromosomes.